Patient-Physician Relational Continuity and Health System Utilization Among Albertans - Patil, Tanmay; Shahid, Rizwan; Patel, Alka; Oddie, Scott (International Journal of Population Data Science, 2018)
Introduction The Office of the Auditor General report on Chronic Disease Management in 2014 identified that in Alberta there are no processes to identify individuals with chronic diseases who do not have or cannot find a Primary Health Care (PHC) physician, and provide them with ongoing care. Objectives and Approach Linked provincial administrative data (Practitioner Claims, National Ambulatory Care Reporting System, Discharge Abstract Database, Clinical Risk Groupers) to identify Albertans with chronic disease who do not have any contact or have low relational continuity with primary care physicians, and examine their healthcare utilization (Hospitalizations, Ambulatory Care Sensitive Conditions, 30-day Hospital Readmissions, Emergency Department visits, and Family practice Sensitive conditions). Usual Provider Continuity index was used to measure relational continuity. Used GIS software to combine findings from secondary data analysis and produced an interactive Online Mapping Application. Ongoing spatial and regression analysis will examine relationship between relational continuity and healthcare utilization. Results The majority of individuals in Alberta with no or low primary care visits were men (62.6%), did not have a chronic disease (94.9%), and belonged to the healthy or healthcare non-user status. Albertans were grouped based on patient-physician relational continuity, and it was seen that the likelihood of emergency department visits and 30-day readmissions declined with increase in continuity, however similar results were not seen in case of hospitalizations. To promote utilization of findings an Online Mapping Application was used to present population groups and their characteristics. Univariate and multivariate analysis will be conducted to examine relation between relational continuity and healthcare utilization, especially usage that could be avoided through regular contact with primary care, while controlling for socio-demographic and health related factors. Conclusion/Implications The results emphasize that the focus should not be on those with no or low number of primary care visits. Strategies focused on linking patients to PHC services and fostering patient-provider relationship are critical to meet the health needs of Albertans and create efficiencies in health system utilization.